Person–Environment–Occupation (PEO) Approach to Managing Sleep Disorders in Older Adults with Hypertension - Endang Sri Wahyuni; Umy Yonaevy; Roh Hastuti (Al-Hijrah Indonesia, 2026)
Hypertension and sleep disorders significantly impact older adults' quality of life and daily functioning. Sleep quality is influenced by physical health, environmental, and occupational factors. The Person–Environment–Occupation (PEO) model provides a comprehensive framework for exploring these interactions. This study examined the relationship between blood pressure and sleep quality in older adults and illustrated the application of the PEO approach in managing sleep disturbances among hypertensive elderly individuals. Using a quantitative analytic observational design with cross-sectional methods, research was conducted in Boyolali involving 30 older adults selected through purposive sampling. Data collection included demographic questionnaires, Pittsburgh Sleep Quality Index (PSQI), and blood pressure measurements using OMRON HEM-7121 digital sphygmomanometer. Data analysis utilized Pearson correlation and descriptive statistics guided by the PEO framework. Findings revealed 70% of participants had hypertension, and 63.3% experienced poor sleep quality. Significant positive correlations were observed between systolic blood pressure and PSQI scores (r=0.72; p=0.001) and between diastolic blood pressure and PSQI scores (r=0.65; p=0.002). Participants with hypertension demonstrated poorer sleep quality than those without hypertension. According to the PEO model, sleep disturbances were influenced by person-related factors (hypertension, stress, fatigue), environmental factors (lighting, noise, family support), and occupational factors (daily routines, sleep hygiene, activity balance). In conclusion, significant associations exist between blood pressure and sleep quality in older adults. The PEO approach serves as a holistic occupational therapy framework, enhancing sleep quality and overall well-being through interventions including sleep hygiene education, stress management, environmental adjustments, and activity regulation.